Effect of Different Surface Treatment Methods on the Shear Bond Strength of Resin Composite/Zirconia for Intra-oral Repair of Zirconia Restorations - Fathpour, Kamyar; Nili Ahmadabadi, Mahsa; Atash, Ramin; Fathi, Amir Hossein (European Journal of Dentistry, 2022)
Objective A durable resin/zirconia bond is essential for successful intra-oral repair of zirconia restorations. The purpose of this study was to evaluate the influence of two mechanical treatments followed by seven chemical treatments on the shear bond strength (SBS) of composite resin to zirconia.Materials and Methods In this in vitro study, 280 zirconia blocks (Y-TZP) were either air-abraded or bur roughened and divided into seven experimental groups (n = 20) in terms of primer/resin application: 1) ZPP, Z-Prime Plus; 2) ZPP + GP, Z-Prime Plus followed by G-premio bond; 3) ZPP + ALB, Z-Prime Plus followed by All Bond Universal; 4) ZPP + CLRF, Z-Prime Plus followed by Clearfil SE Bond; 5)GP, G-Premio Bond 6) ALB, All Bond Universal; and 7) CLRF, Clearfil SE Bond. After composite bonding and storage in distilled water (24 hours), half of each group specimen (n = 10) were thermocycled. All specimens were subjected to shear force. Statistical analysis was performed using Kruskal–Wallis and Mann–Whitney test (α = 0.05).Results Significant reduction in SBS was observed in all groups after thermocycling(p < 0.05), except for the air-abraded ZPP + CLRF (p = 0.143). After aging, air-abraded CLRF exhibited the highest SBS (13.55 ± 7.8 MPa) and bur roughened ZPP showed the lowest SBS (1.16 ± 1.23 MPa). In the aged specimens, there was a significant difference between air abrasion and bur roughening in all groups (p < 0.05).Conclusion Air-abrasion followed by application of adhesive (with/without prior primer application) is the most efficient technique for repair of veneered zirconia restorations with resin composite.
Keywords: zirconium; Clearfil SE bond; shear bond strength